La comprensión lectora en el rendimiento de los estudiantes del 5°, 6° y 7° de educación básica, en el área de lenguaje y literatura, de la escuela Rafael j. Bazante del cantón Chimbo, provincia Bolívar período lectivo 2014-2015 - Montufar Santamaría, Verónica Adriana (2015)
Rafael J Bazante school children and 5th, 6th and 7th year of basic education is studying the institution have a reading comprehension and academic performance that can be described as fair and therefore a problem in the future in their later stages of secondary study and higher. My proposal aims to contribute to improve this area of reading comprehension with the application of a dynamic strategy and a tutorial with the use of metaphors designed to improve performance in each of the students involved in this research. Research methods will be used as they are deductive, inductive, historical, scientific, analytical and descriptive, statistical and historical, also techniques for data collection and evaluation and survey method for this research, which allowed detecting fundamentals for development and production of the thesis. Students of the 5th, 6th and 7th year of basic education survey was conducted to obtain information used to develop conclusions and recommendations which shows mostly regular level when reading a text and to understand what It can be defined as a regular school performance since it is a basic tool to acquire knowledge through reading. The proposal is built and developed with information strictly School Rafaela J Bazante Canton Chimbo. It has developed a strategy with a set of scheduled supervised activities for which they meet the objectives, strictly involving the study population is students and teachers of the school in question allowing gradually improves reading comprehension. The strategy applied to become a tactical instrument to improve the acquisition of knowledge through reading